The Role of Cultural Competence in Ethnopsychiatric Nursing: A Systematic Review of Practice, Education, and Patient Outcomes - Fatma Lutfiyatus Sayyida; Anggun Novia Indah Fitri; Indi Dwi Shofi Yanti (Tarqabin Nusantara Group, 2025)
Cultural competence is a critical component of effective psychiatric nursing, particularly in ethnopsychiatry, where cultural context significantly influences the expression, diagnosis, and treatment of mental illness. This systematic review explores how culturally competent care enhances clinical interactions, improves patient outcomes, and reduces health disparities in multicultural mental health settings. Drawing on 25 peer-reviewed studies published between 2005 and 2025, the review synthesizes evidence using PRISMA guidelines and integrates theoretical frameworks such as Campinha-Bacote’s Model of Cultural Competence and the Staircase Model to analyze key domains influencing nursing practice. Findings reveal that cultural competence strengthens the therapeutic alliance, facilitates accurate diagnosis through tools like the Outline for Cultural Formulation (OCF), and supports patient-centered treatment planning. Effective communication strategies, including the use of interpreters and cultural brokers, are shown to improve trust and treatment adherence, especially among vulnerable populations such as refugees and non-Western migrant communities. The study also underscores the role of cultural competence in reducing racial and ethnic disparities by increasing awareness of implicit bias and promoting equitable service delivery. Institutional support, including language access programs and inclusive policies, is essential for embedding cultural competence into everyday practice. Furthermore, integrating cultural content into nursing education and continuing professional development ensures that nurses are equipped to navigate cross-cultural challenges throughout their careers. Despite the growing recognition of its importance, empirical evidence measuring the direct impact of cultural competence on clinical outcomes remains limited, highlighting the need for further research and standardized evaluation tools. In conclusion, this review affirms that cultural competence is not an optional skill but a fundamental requirement for delivering respectful, equitable, and effective mental health care in increasingly diverse societies.